Regulation of Effector and Memory CD8 T Cell Differentiation by IL-2—A Balancing Act - Kalia, Vandana; Sarkar, Surojit (Frontiers in Immunology, 2018)
Interleukin-2 (IL-2) regulates key aspects of CD8 T cell biology – signaling through distinct pathways IL-2 triggers critical metabolic and transcriptional changes that lead to a spectrum of physiological outcomes such as cell survival, proliferation and effector differentiation. In addition to driving effector differentiation, IL-2 signals are also critical for formation of long-lived CD8 T cell memory. This review discusses a model of rheostatic control of CD8 T cell effector and memory differentiation by IL-2, wherein the timing, duration, dose and source of IL-2 signals are considered in fine-tuning the balance of key transcriptional regulators of cell fate.